Economic Linkage and the Contagion Effect of Earnings Quality on Market Risk - Hashemi Tonekaboni, Javad; Khosravipour, Negar; Farsad Amanollahi , Gholamreza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study investigates the economic linkage and contagion effect of earnings quality on market risk at the Tehran Stock Exchange over the years 2010 to 2019, focusing on a screened statistical population consisting of 650 (year-company) data points. Given the concept of information transfer and previous studies related to earnings quality, it is hypothesized that higher earnings quality among industry peers (comprising a subset of closely related companies based on industry classification at the stock exchange) reduces a company's systematic risk.Methodology: This research employs three different metrics for measuring earnings quality and uses multivariate regression for hypothesis testing and model estimation.Findings: The results indicate that the estimated coefficients for earnings quality of the company (-0.011825) and related companies (-0.025110) are inversely related.Conclusion: The results suggest that higher earnings quality among economically linked companies leads to a reduction in a company's systematic risk.